The Development of Discovery Learning Based Student’ Worksheet on Topic Quantity, Measurements and Vectors - Muhammad Ridlo Ilahi; Bahtiar Bahtiar; Muhammad Zaini (Department of Physics Education, Universitas Mataram, 2022)
This research is in the background of the author's concerns about the teaching and learning process in schools, educators are more dominant than students, shown by the way used by educators when the teaching and learning process still uses the lecture method by giving percentages and practice questions to students and students do not experiment at all in the teaching and learning process so that students have not been very active in building concepts in learning that has taken place In learning curriculum 2013 students are required to be more active in building concepts through scientific approaches such as analyzing, associating, collecting information, questioning, observing and telling about what they have found in the teaching and learning process carried out between educators and students This type of research uses research methods of development or Research and Development (R&D). The development research method is a research method used to produce a certain product, and test the effectiveness of the product. The results showed that the feasibility of LKPD based on discovery learning on the material of the measurement and vector quantity that had been developed by researchers according to the assessment of media experts as a whole got a score of 71% in the feasible criteria. Meanwhile, based on the assessment of experts, the material as a whole got a score of 90% in the criteria is very feasible while the response of students to LKPD based on discovery learning on the material of the measurement and vector quantities that have been developed as a whole gets a score of 89% included in the criteria is very interesting.